Manajemen unit usaha syariah dalam pengembangan kultur dan karakter wirausaha berbasis pesantren di Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Abdulloh Ahid (FADZAT: Jurnal Ekonomi Syariah, 2020)
The objectives of this study are: 1) To analyze the culture and character of entrepreneurship based on Islamic boarding schools which have a simultaneous effect on the management of Islamic business units 2) To analyze the culture and character of entrepreneurship based on Islamic boarding schools which have a partial effect on the management of Islamic business units 3) to analyze the cultural variables and entrepreneurial characters based on the pesantren which has a dominant effect on sharia business unit management. This study uses quantitative descriptive analysis with explanatory research. The number of respondents in the population is 53 people as a saturated sample. In this study the authors used multiple linear regression analysis techniques. From the research results it can be concluded as follows: 1) The culture and character of entrepreneurship based on the pesantren simultaneously influence the management of sharia business units. 2) Entrepreneurial culture and character based on pesantren partially influences sharia business unit management. 3) The pesantren-based entrepreneurial culture has the most dominant influence on sharia business unit management.